Does complex hydrology require complex water quality policy?1. (9th November 2013) - Anastasiadis, Simon; Kerr, Suzi; Nauleau, Marie‐Laure; Cox, Tim; Rutherford, Kit
<x xml:space="preserve">Abstract</x> Nonpoint‐source water pollution is frequently considered intractable because it is hard to regulate large numbers of small sources and because the science associated with assessing the impact of each source is complex. New Zealand has demonstrated that it is possible to implement a simple cap‐and‐trade system to help reduce nitrogen leaching from many small farms and thereby protect water quality. This paper relates to the second challenge: are complex regulatory systems worthwhile when nitrogen delivery is complex? When nitrogen moves through groundwater to a lake, leaching from different farms reaches the lake at different times and the damage caused is temporally differentiated. Policy that regulates farmers according to the timing of their nitrogen delivery will be more complex than policy that does not. Whether the gain in efficiency justifies this additional complexity can be assessed through modelling. We use an integrated model to estimate the gains from complex nitrogen regulation that incorporates groundwater delivery times relative to simple nitrogen regulation that does not. We find that the gains from more complex regulation are small in the catchment we study and cannot justify the additional complexity required. A sensitivity analysis enables us to identify the types of catchments where complex regulation may be worthwhile.